A comparative diagnostic yield among cytologic examination, cell block and closed pleural biopsy in exudative pleural effusion - Chumpangern, Worawat; So-ngern, Apichart; Toomsongkram, Praewpanit; Chaisuriya, Nipon; Reechaipichitkul, Wipa; Arunsurat, Itthiphat; Ratanawatkul, Pailin (Journal of thoracic disease, 2024)
Cytology, cell block, and closed pleural biopsy are the initial investigations for exudative pleural effusion. However, the study of the diagnostic yield of the combination of methods is limited. The objective is to compare the diagnostic yield of cytology, cell block, and closed pleural biopsy with that of cytology and cell block. A retrospective cross-sectional study was conducted between 1 January 2014 and 31 March 2020 at Srinagarind Hospital, Thailand. The study included subjects with undiagnosed pleural effusion who had cytology, cell block, and closed pleural biopsy results. The study included 175 subjects with exudative pleural effusions. One hundred and thirty-eight malignant pleural effusions (78.9%) and 34 tuberculous pleural effusions (19.4%) were diagnosed. One hundred and forty-two patients could be diagnosed by either method. Cytology, cell block, and closed pleural biopsy had 40.6%, 36.0%, and 58.3% diagnostic yields, respectively. Compared with cytology alone, 49.1% of the diagnostic yield was increased with cytology and cell block (P<0.001) and 81.1% with closed pleural biopsy, cell block, and cytology (P<0.001). In malignant pleural effusions, cytology, cell block, and closed pleural biopsy yielded 51.4%, 45.7%, and 56.5%, respectively. Combining the three methods increased to 85.5% compared with cytology alone (P<0.001). Seventeen patients (10%) had complications associated with thoracentesis and closed pleural biopsy, of which 6.9% resulted in pneumothorax. A combination of closed pleural biopsy, cell block, and conventional cytology provided favorable diagnostic yields in patients with exudative pleural effusion.